HORMONAL CONTRACEPTION AND THE RISK OF DEPRESSIVE SYMPTOMS: A LITERATURE REVIEW - Filip Kochański; Barbara Starosta; Magdalena Bartold; Marta Piotraszewska; Magda Skudzińska; Karolina Wołk; Aleksandra Jaskulska; Jan Pietrzak; Dominika Błonka; Janina Pohrybieniuk (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Hormonal contraception (HC) is a method widely used for pregnancy prevention among adolescents and adult women. It is also prescribed to manage menstrual and dermatological symptoms. Despite its popularity, concerns have been raised regarding potential mental health side effects, particularly the risk of developing or worsening depressive symptoms. Existing research has produced mixed results—some studies suggest a possible association between HC use and an increased risk of depression, especially among younger users, while others report no significant link or even indicate a protective effect.Aim of the Study: This literature review aims to evaluate current evidence regarding the relationship between HC use and the occurrence of depressive symptoms, with particular emphasis on adolescent girls and young women. By examining available research, the review seeks to clarify the potential psychological risks associated with different forms of hormonal contraception.Conclusions: The findings of the cited studies suggest that the use of HC, especially during adolescence, may be associated with an increased risk of developing depressive symptoms. However, the evidence is not uniform—some studies do not confirm this negative effect, while others highlight the role of individual vulnerability. Further research is necessary to better understand the mechanisms underlying these associations and to support a more personalized approach to contraceptive counseling, particularly for young women at increased risk of mood disorders.